Benefit of Cognitive Stimulation Therapy in a Patient with Vascular Dementia: A Case Report - Soedirman, Billy Salvatore; Laksmidewi, Anak Agung Ayu Putri (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Cognitive stimulation therapy (CST) is a restoration therapy based on cognitive improvement of patients, by giving patients a variety of stimulation. This therapy is highly recommended for people with mild dementia from mild to moderate in either Alzheimer dementia or vascular dementia. Vascular dementia is a collection of symptoms of decreased cognitive abilities associated with the incidence of stroke. CASE REPORT: Reported a 76-year-old man, who had a bleeding stroke, in admission the patient were often angry, sleepless, and aphasic. After returning home the patient experienced impairment in memory, language, executive ability, mild to moderate degree of visuospatial and incapable to manage his daily activities, therefore in routine evaluation of the 3rd month, patient was diagnosed as Vascular cognitive impairment. On regular home visits until the 6th month after the stroke, it was reported that in the first 6 months had been received CST. However, in the 7th–9th month of CST because at the time of the coronavirus disease-19 pandemic, human interaction was severely restricted, so patient monitoring was carried out using Ina AD-8 through phone. An evaluation of the cognitive function by measuring the cognitive function of the patient was using the Indonesian version of Montreal Cognitive Assessment (MoCA-Ina), as well as using activity daily living and instrumental daily living activities to measure the patient’s independence function. After 6 months of CST, there were cognitive improvements and were seen in MoCA – Ina, Ina AD-8 followed by improved patient independence. CONCLUSION: Cognitive stimulation is the best intervention option in the treatment of mild to moderate vascular dementia. This case is one good example that shows the success of CST that has been observed for 9 months, not only on the cognitive component but also in terms of the ability to perform daily activities.